Rancang Bangun Sistem Informasi Penggajian Karyawan PT. Sinar Mentari Era Jaya - Miwan Kurniawan Hidayat; Ishak Komarudin; Cicilia Regita Valent Cicilia Regita Valent; Adjat Sudradjat; Retno Sari (IMTechno: Journal of Industrial Management and Technology, 2021)
So far, the payroll system of PT. Sinar Mentari Era Jaya runs manually, so that even miscalculations cannot be avoided. This results in inconvenience for employees at work, which in turn can reduce the work productivity of the employees themselves. Given these problems, it is necessary to build a computerized payroll system using a programming application that can simplify the work of the HRD department, making it more effective and efficient. PT's payroll information system. Sinar Mentari Era Jaya is made with MySQL DBMS and the PHP programming language is used to manage employee data, work attendance, holidays, as well as to perform salary calculations based on the data that has been inputted, and can be used to print reports. Finally, with this payroll information system, the salary calculation process can be done automatically without the need to calculate manually and the salary data obtained is appropriate, provided that all data entered is valid.